2015
DOI: 10.1371/journal.pone.0143187
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Atherosclerotic Plaque Detected by Computed Tomographic Angiography in Subjects with Diabetes Compared to Those without Diabetes

Abstract: ObjectivesLittle data are available regarding coronary plaque composition and semi-quantitative scores in individuals with diabetes; the extent to which diabetes may affect the presence and extent of Coronary Artery Calcium (CAC) needs more evaluation. Considering that this information may be of great value in formulating preventive interventions in this population, we compared these findings in individuals with diabetes to those without.MethodsMulti-Detector Computed Tomographic (MDCT) images of 861 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Total Agatston score was higher in diabetic patients (440 ± 786 vs 195 ± 404, P < 0.001) ( 5 ). Khazai et al found that segment involvement score, segment stenosis score, and total plaque score were higher in diabetics but there was no significant difference in the number of non-calcified plaque between the two groups ( 50 ). In one study by Pundziute et al, diabetics showed more diseased segments and more segments with non-obstructive CAD, but Agatston score was similar between the two groups ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Total Agatston score was higher in diabetic patients (440 ± 786 vs 195 ± 404, P < 0.001) ( 5 ). Khazai et al found that segment involvement score, segment stenosis score, and total plaque score were higher in diabetics but there was no significant difference in the number of non-calcified plaque between the two groups ( 50 ). In one study by Pundziute et al, diabetics showed more diseased segments and more segments with non-obstructive CAD, but Agatston score was similar between the two groups ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…30, 31 Progressive atherosclerotic lesions (i.e. pathological intimal thickening and early fibroatheroma) with micro-calcification cannot be identified by CT, 32 whereas late obstructive coronary artery disease is strongly associated with a high CAC score (Agatston score ≥400).…”
Section: Calcification and Coronary Artery Disease Risk In Diabeticsmentioning
confidence: 99%
“…While IVUS is a robust method for determining plaque morphology in vivo, it cannot determine plaque composition with chemical specificity. This is of particular interest, as diabetes is associated with lipid laden plaques that are more vulnerable to rupture [ 50 ]. Intravascular photoacoustic ultrasound includes morphological imaging and has chemical specificity to determine lipid content inside atherosclerotic plaque [ 51 54 ].…”
Section: Discussionmentioning
confidence: 99%